2018
DOI: 10.1055/s-0037-1612618
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nonabsorbable Spiral Tacks for Mesh Reinforcement in Thoracoscopic Repair of Congenital Diaphragmatic Hernia

Abstract: Thoracoscopic prosthetic repair of congenital diaphragmatic hernia (CDH) is a well-established and safe technique in experienced hands but the patching procedure is technically demanding and time consuming. To address the challenges associated with this process (confined working space and restricted time), the aim of this article is to assess the potential improvements in feasibility, efficacy, and safety of patch fixation by using nonabsorbable helicoidal tacks in neonates and infants for the repair of large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The present case is the first successful pediatric laparoscopic repair of a Morgagni hernia that was accomplished by using sprial tacks for mesh fixation. Spiral tacks were also used for mesh reinforcement during the thoracoscopic repair of a posterolateral (Bochdalek) hernia in two infants 7 . However, there has been mounting criticism about the use of tacks in the diaphragm because of the potential for cardiac injury 8 .…”
Section: Discussionmentioning
confidence: 99%
“…The present case is the first successful pediatric laparoscopic repair of a Morgagni hernia that was accomplished by using sprial tacks for mesh fixation. Spiral tacks were also used for mesh reinforcement during the thoracoscopic repair of a posterolateral (Bochdalek) hernia in two infants 7 . However, there has been mounting criticism about the use of tacks in the diaphragm because of the potential for cardiac injury 8 .…”
Section: Discussionmentioning
confidence: 99%
“…12 Nasr et al reported data from four different patch types-Gore-Tex, Marlex, Surgisis, and Silastic-and showed that Surgisis had the lowest recurrence rate of 20%, although it also had the smallest sample size of only five patients. 17 Tsai 2012, 18 Romao 2012, 14 Riquelme 2016, 19 Riehle 2007, 20 Premkumar 2015, 21 Poupalou 2018, 22 Mitchell 2008, 15 Loff 2005, 7 Jancelewicz 2010, 6 Jancelewicz 2013, 12 Glick 1992, 23 de Kort 1996, 24 Cantone 2014, 25 Becmeur 2001, 26 Barnhart 2012, 16 Yokota 2014, 27 Long 2019, 8 Grethel 2006, 5 Heiwegen 2020, 28 Guner 2008, 29 Dewberry 2019, 37 D'agostino 1995, 31 Baerg 2012, 32 Total synthetic 493 49 9.9…”
Section: Recurrence Rate-studies Comparing Synthetic To Biological Pa...mentioning
confidence: 99%
“…Single case reports Shariff 2014, 33 Riquelme 2015, 19 Premkumar 2015, 21 Hutson 1985, 35 Gander 2010, 41 Davis 2002, 42 Cantone 2014, 25 Bruen 2007, 36 Becmeur 2001, 26 Bawazir 2019 43 22 Glick 1992, 23 Ahmed 1998 44 Retrospective case series with research questions and outcomes Yokota 2014, 27 Weaver 2006, 45 Tsai 2012, 18 Shah 2009, 46 Russel 2014, 40 Romao 2012, 14 Riehle 2007, 20 Razumovskly 2016, 11 Nasr 2010, 17 Mitchell 2008, 15 McHoney 2010, 47 Loff 2005, 7 Laituri 2010, 13 Kuklová 2011, 38 Koziarkiewicz 2014, 39 Koot 1993, 48 Kamran 2018, 49 Jawaid 2013, 9 Janssen 2018, 30 Jancelewicz 2013, 12 Grethel 2006, 5 Heiwegen 2020, 28 Guner 2008, 29 Dewberry 2019, 37 de Kort 1996, 24 D'agostino 1995, 31 Cho 2009, 50 Barnhart 2012, 16 Baerg 2012, 32 Aydin 2020 51 34 Rygl 2012, 52 Long 2019, 8 Jancelewicz 2010 6 Four studies (132 patients total) that systematically reported death rates in treated patients were included in the table. Death rates for synthetic patches ranged from 19 to 32%, whereas...…”
Section: Characteristics Of Studies Assessment Of Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…In neonates with a small diaphragm defect, primary repair can be used to close the diaphragm with sutures. In neonates with a large defect that does not allow primary repair, patch repair can be used to close the diaphragm with synthetic materials …”
mentioning
confidence: 99%